2014
DOI: 10.1542/peds.2014-1279
|View full text |Cite
|
Sign up to set email alerts
|

Parental Financial Incentives for Increasing Preschool Vaccination Uptake: Systematic Review

Abstract: BACKGROUND AND OBJECTIVE: Financial incentives have been used to promote vaccination uptake but are not always viewed as acceptable. Quasimandatory policies, such as requiring vaccinations for school enrollment, are widely implemented in some countries. A systematic review was conducted to determine the effectiveness, acceptability, and economic costs and consequences of parental financial incentives and quasimandatory schemes for increasing the uptake of preschool vaccinations in high-income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…A more detailed understanding of what aspects of acceptability of health-promoting financial incentives are common across all settings and which are context-specific -as well as what determines context-specific differenceswould be helpful. Our results support findings from US studies and the current systematic review around the acceptability of quasi-mandatory schemes for increasing the uptake of vaccination, 56 suggesting that the introduction of such schemes, with the inclusion of an opt-out system, would be acceptable to parents and professionals, and could encourage the normalisation of vaccination while being equitable for parents across the socioeconomic spectrum.…”
Section: Comparison With Previous Worksupporting
confidence: 86%
“…A more detailed understanding of what aspects of acceptability of health-promoting financial incentives are common across all settings and which are context-specific -as well as what determines context-specific differenceswould be helpful. Our results support findings from US studies and the current systematic review around the acceptability of quasi-mandatory schemes for increasing the uptake of vaccination, 56 suggesting that the introduction of such schemes, with the inclusion of an opt-out system, would be acceptable to parents and professionals, and could encourage the normalisation of vaccination while being equitable for parents across the socioeconomic spectrum.…”
Section: Comparison With Previous Worksupporting
confidence: 86%
“…The search strategy yielded 15 literature reviews or metaanalysis that met the eligibility criteria [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The majority of these were published in the last 3 years (9/15).…”
Section: Resultsmentioning
confidence: 99%
“…Both of these reviews included almost exclusively studies conducted in the United States. Williams, after reviewing the effectiveness of 15 interventions to improve attitudes, vaccination intent or vaccine uptake, was unable to identify any type of intervention as being more effective than others [24]. She also noticed that few studies identified parents as vaccine-hesitant prior to participation [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations